TINGKAT KEBUGARAN JASMANI SISWA KELAS ATAS DI SD NEGERI 11 REGANG AGUNG DAN SEKOLAH DASAR NEGERI 40 PERCONTOHAN PANGKALAN BALAI KECAMATAN BANYUASIN 3 KABUPATEN BANYUASIN - Winata, Ridwan Andri (Jurnal PGSD Musi, 2018)
Physical fitness plays a very important role in human activities. With physical fitness a person can do all activities well. The problem in this research is how the level of physical fitness of the Upper Class students at the 11 Regang Agung Public Elementary School and the State Elementary School 40 Pilot Base Station in the Banyuasin District 3 Banyuasin District. The purpose of this study was to describe the level of physical fitness of top students at 11 Regang Agung Elementary School and Public Elementary School 40 Pilot Base Station in Banyuasin District 3, Banyuasin District. The results showed that the description of the physical fitness level of upper class students at SD Negeri 11 Regang Agung and Public Elementary Schools 40 Pilot Base Pangkalan Balai District Banyuasin 3 Banyuasin District averaged in the medium category. The details of the test results are: a) very good category of 3 students with a percentage of 3.16%. b) good categories as many as 21 students with a percentage of 22.11%. c) moderate category as many as 60 students with a percentage of 63.16%. d) less categories as many as 9 students with a percentage of 9.47%. e) very few categories as many as 2 students with a percentage of 2.11%.